Pescadores artesanais e violência na Baía de Guanabara - Ferreira, Cesar Bernardo (2019)
This thesis presents a qualitative ethnographic study on the cases of violence reported by artisanal fishermen during their work in Guanabara Bay, Rio de Janeiro. The general objective was to investigate how violence interferes in the work of the artisanal fisherman, seeking to characterize the cases of violence; identify the subjects, times and spaces involved in these cases; and to establish connections between the cases of violence, the current economic model and the public policies for Guanabara Bay. The sample was constructed using the methodology known as "snowball", starting with the leaders of the colonies. The instruments for data collection were participant observation and semi-structured interviews. We interviewed 20 artisanal fishermen, two from the Z-8 Colony, five from the Z-9, four from the Z-10, four from the Z-11, two from the Fishermen's Association of Tubiacanga, two fishers without affiliation and a representative from FEPERJ. Observations were recorded in field notes and interviews recorded in audio and transcribed. The analysis of the data occurred through a thematization process. Results indicate that the reported cases of violence are strongly related to the advance of economic activities on the fishing sites and collection traditionally used by fishermen. A deterritorialization occurs when these workers are forced to change their daily practices by virtue of the interests of the state and agents of the capital. We have noticed the existence of a multiterritoriality, of complex configuration, where artisanal fishermen, the Brazilian Navy, the petrochemical industries and other organizations and individuals working in Guanabara Bay, both in the surroundings and in the mirror of water, are marked by conflicts, which often result in the physical death of the fisherman. We argue that artisanal fishermen in Guanabara Bay suffer from bioethnic violence, ranging from the annihilation of ecosystems to the epistemicity of the ethnic groups to which they belong, including various forms of cultural, labor and existential annihilation of these men and women. Research indicates that the advance of capitalist activities and increasing metropolization underlies bioethnic violence in Guanabara Bay, which includes water pollution, fish disappearance, habit changes, name-calling, bullet-shooting, assassination, social invisibility, among other acts against the fisherman and its territory. We conclude that despite these cases of violence, fishermen fight for the right to live and work according to their traditions. Despite the violence, they continue to be seen among offshore vessels, shipyards, petrochemical poles and pollutant patches floating on the Guanabara water mirror. They persevere in guaranteeing their right to work and to life.